2020
DOI: 10.1111/nin.12351
|View full text |Cite
|
Sign up to set email alerts
|

Demystifying the mirror taboo: A neurocognitive model of viewing self in the mirror

Abstract: Research has consistently demonstrated that viewing one's body in a mirror after an amputation or other perceived or visible body disfigurements can be a traumatic experience. Mirror viewing or mirroring is a taboo subject, which may be the reason this trauma has not been previously detected or acknowledged. Traumatic mirror viewing may lead to mirror discomfort, mirror avoidance, and a host of psychosocial concerns, including post-traumatic stress. As mirroring is complex, four qualitative mirror viewing stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…Looking in the mirror elicited negative emotional responses, with some survivors avoiding the mirror for weeks after treatment. This has been termed 'mirror trauma' [47] and has been explained as a significant autonomic nervous system shock reaction via the polyvagal response [48]. Earlier research has found similar shock at first sight [41,49], with those who avoid looking in the mirror, likely to experience delayed adaptation [50].…”
Section: Discussionmentioning
confidence: 99%
“…Looking in the mirror elicited negative emotional responses, with some survivors avoiding the mirror for weeks after treatment. This has been termed 'mirror trauma' [47] and has been explained as a significant autonomic nervous system shock reaction via the polyvagal response [48]. Earlier research has found similar shock at first sight [41,49], with those who avoid looking in the mirror, likely to experience delayed adaptation [50].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, this study was excluded from the review as it did not include the term ‘mirror’ in the body of the text; however, the results mimic the comments from women described in this review. According to Freysteinson's (2020) Neurocognitive Mirror Viewing Model, anticipatory fear of what one may look like in the mirror can be accompanied by an autonomic nervous system response that may result in mirror viewing discomfort. This model correlates with our review findings as women described how their apprehension of not knowing what to expect led them to initially avoid mirrors (Freysteinson et al, 2012; Gershfeld Litvin & Jacoby, 2020; Menon & O'Mahony, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Viewing one's post-mastectomy body can be an emotionally charged experience with variable reactions. In this review, women described feelings of shock and numbness as they looked in the mirror (Davies et al, 2017;Freysteinson et al, 2012;Gershfeld Litvin & Jacoby, 2020;Herring et al, 2019;McKean et al, 2013), similar to the autonomic nervous system fright/flight and faint response described in Freysteinson's (2020) Neurocognitive Mirror Viewing Model. Women also reported how they did not recognize themselves in the mirror (Brunet et al, 2013;Gershfeld-Litvin, 2021;Kocan & Gursoy, 2016;Olasehinde et al, 2019), signifying short-term memory dysfunction, where the mind cannot register self-recognition, another aspect of the Mirror Viewing Model.…”
Section: Themes Sub-themes Codesmentioning
confidence: 91%
See 1 more Smart Citation
“…The mirror is a reflective aspect made of glass and coated with amalgam and reflects a clear image (Dictionary.com, 2020). It offers a visual field that is seen in the first person and can have a straight observation of ourselves (Freysteinson, 2020). Mirror exposure therapy is a methodical repetitive observation of oneself in a mirror with distinct guidance (Griffen et al, 2018).…”
mentioning
confidence: 99%